Homocysteine as a Risk Factor for Atherosclerosis - Mohamed, Mohamed Younes (faculty of Basic Medical Science - Libyan International Medical University, 2018)
This study aimed to review the role of homocysteine as a risk factor in the pathogenesis of atherosclerosis and atheroma, and to provide recommendations for the treatment of hyperhomocysteinemia.
Homocysteine is a sulphurated amino acid which, at high plasma concentrations, predisposes to thrombosis and induces focal arteriosclerosis. These characteristics have been established both in patients with homocystinuria, a genetic disease in which homocysteine accumulates in the blood.(1) In addition it must be emphasized that the vascular disease in homocystinuria due to cystathionine β-synthase (CBS) deficiency, methylenetetrahydrofolatereductase (MTHFR) deficiency, or inborn errors in cobalamin metabolism bears little resemblance to the atherosclerotic and atherothrombotic vascular disease seen in the adult general population. Atherosclerosis is characterized by a thickening of the arterial wall due to smooth muscle cell proliferation, lipid deposits, and fibrosis.(2)Rupture of the lipid-containing atherosclerotic plaques results in thrombosis (atherothrombosis) and leads to myocardial infarction and stroke.The first indication that sulfur amino acid metabolism is linked to atherosclerosis came from observations in 1953 demonstrating that pathogenic cholesterol concentrations and experimental atherogenesis in monkeys can be inhibited by dietary methionine(3). Since the early 60s elevated homocysteine levels in blood (hyperhomocysteinemia) caused by different deficiencies of sulfur amino acid metabolism were reported to be associated with vascular disease and, in particular, with atherosclerotic plaque formation. Today, Hcy is recognized by many studies as a strong, independent and causal risk factor for atherosclerosis.